DAMPAK JALUR PELABUHAN BAGI PENDIDIKAN ANAK SEKOLAH DASAR (Studi kasus peserta didik di SDN 03 Sintete) - Ilma Sholeha; Ayu Sholina (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2020)
This study was motivated by low motivation of students This study aims to find out the impact of port lane as social environment so that it has impact on education in SDN 03 Sintete because most of students live around the port. The study used qualitative approach and data collection techniques used were observation, interview and documentation. Sampling technique used is sampling purposive that determination of the sample based on certain consideration. The result showed that port lane had positive impact on the socioeconomic society in Sintete. However, port lane also had negative impact for student’s education in SDN 03 Sintete.